Marsh Fritillary (Euphydryas aurinia) in the Czech Republic: monitoring, metapopulation structure, and conservation of an endangered butterfly - Hula, Vladimir; Konvička, Martin; Pavlicko, Alois; Fric, Zdenek (Entomologica Fennica, 2004)
Thirty colonies of the Marsh Fritillary (Euphydryas aurinia) have recently been recorded in Western Bohemia, Czech Republic. The majority of colonies are small, their total area are 1.5 km2. Small size and intensive grazing/mowing were positively associated with observed declines/extinctions, while abandonment threatens the colonies in the longer term. Short distances to nearest colonies buffered against declines. High colony turnover, asynchronous local dynamics pointed and the species’ biotope requirements all point to a dynamic metapopulation structure; patterns of connectivity revealed that there are several metapopulations within the region. Because conserving the species within its extant sites seems unsustainable in the long term, restoration of its habitats is proposed.